2019
DOI: 10.1186/s12302-019-0212-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyanobacterial toxins on the human gastrointestinal tract and the mucosal innate immune system

Abstract: Background: Cyanobacterial blooms occur with increasing frequency in freshwater ecosystems, posing a hazard to human and environmental health. Exposure of human to cyanobacterial metabolites occurs mostly via accidental ingestion through contaminated drinking water or during recreational activities and, most frequently, results in gastrointestinal symptoms. Despite the clinical manifestation, cyanobacterial metabolites are rather investigated for their toxicity towards specific organs or tissues, especially he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 187 publications
(246 reference statements)
1
56
0
3
Order By: Relevance
“…In particular, the toxin-producing cyanobacteria genera, including Microcystis and Cylindrospermopsis , as well as Leptospira interrogans can lead to kidney disease 14 , 18 , 24 , 25 and have, therefore, been put forward as potential causes of CKDu 21 , 26 , 27 . Significant increases of cyanobacteria in freshwater resources in Sri Lanka have occurred over the past century as a result of eutrophication and rising temperatures 21 , 28 , demonstrating that altered water chemistry is likely to promote the presence of pathogenic bacteria in this region.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the toxin-producing cyanobacteria genera, including Microcystis and Cylindrospermopsis , as well as Leptospira interrogans can lead to kidney disease 14 , 18 , 24 , 25 and have, therefore, been put forward as potential causes of CKDu 21 , 26 , 27 . Significant increases of cyanobacteria in freshwater resources in Sri Lanka have occurred over the past century as a result of eutrophication and rising temperatures 21 , 28 , demonstrating that altered water chemistry is likely to promote the presence of pathogenic bacteria in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Out of 11 different human OATP isoforms, the ability to transport MC-LR was confirmed for OATP family 1 (OATP1A2, 1B1 and 1B3), while no MC-LR transport was detected for the OATP2B1 [50]. To the best of our knowledge, the other OATP isoforms have not been investigated for their ability to transport MC-LR [36]. Regarding OATP expression in human lung tissue, studies utilizing microarray and RT-PCR reported expression of OATP2B1, 3A1, 4A1, and 4C1 [51,52], while targeted proteomics analyses detected OATP1A2, 1B3, 2A1 and 2B1 [53].…”
Section: Discussionmentioning
confidence: 88%
“…It covers the large surface of the gastrointestinal tract, which is in contact with toxins in water and food, and is the common barrier against their absorption in inner-body fluids. Over the last two decades, the effect of CYN on the gastrointestinal tract has been tested using in vivo and in vitro experimental models (for details see [ 25 ]). A large amount of CYN-containing extract (2.5–8.3 mg/kg) was applied in the in vivo study [ 26 ].…”
Section: Introductionmentioning
confidence: 99%